2019
DOI: 10.2807/1560-7917.es.2019.24.14.1800369
|View full text |Cite
|
Sign up to set email alerts
|

The seroprevalence of untreated chronic hepatitis C virus (HCV) infection and associated risk factors in male Irish prisoners: a cross-sectional study, 2017

Abstract: Introduction Data on chronic hepatitis C (HCV) infection prevalence in European prisons are incomplete and impact the public health opportunity that incarceration provides. Aims We aimed to estimate the seroprevalence of untreated chronic HCV infection and to identify associated risk factors in an Irish male prison. Methods We conducted a cross-sectional study involving a researcher-administered questionnaire, review of medical records and HC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 34 publications
1
15
1
Order By: Relevance
“…We further analyzed these 16 cases, which constitute one of the largest cohorts of HHpgV-1 viremic individuals in the literature. Their demographic characteristics revealed novel potential routes of acquisition such as receiving a tattoo or having sex with men, both recognized risk factors for blood-borne viruses [18, 19].…”
Section: Discussionmentioning
confidence: 99%
“…We further analyzed these 16 cases, which constitute one of the largest cohorts of HHpgV-1 viremic individuals in the literature. Their demographic characteristics revealed novel potential routes of acquisition such as receiving a tattoo or having sex with men, both recognized risk factors for blood-borne viruses [18, 19].…”
Section: Discussionmentioning
confidence: 99%
“…This study is a follow up study from a previously published 2017 cross sectional study that estimated the prevalence of untreated chronic HCV infection and associated risk factors in a male Irish prisoners [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…We observed that there is increase prevalence of hepatitis c disease in males in comparison to female (207, 156 respectively). These observations may also be attributed to the IDU, as males were more affected [44] [45]. Also there is more exposure of males to the environment as compared to females, in our area of study, which may be another contributing factor and hence males were main target.…”
Section: Discussionmentioning
confidence: 78%